The management of loan portolios and the performance of indigenous c ommercial banks in Uganda : a case of Uganda Commercial Bank Limited (UCB) and Centenary Rural Development Bank (CERUDEB) - Ssewagudde, Eva (Kampala, 2000)
Thesis (MBA) - Makerere University, 2000
Includes bibliographical references (p.108-116)
Keywords: Banks and banking -- Uganda; Bank loans -- Uganda